Pesan Moral yang Terdapat dalam Novel Paper Towns Karya John Green - Widya Aulia Pratiwi Rahmah (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2024)
Novel is a literary of work which contains a moral message. In every story there must be a good lesson that we can apply in everyday life. One of them is the novel Paper Towns by John Green which makes it interesting for researchers to examine